Sustainable solar energy conversion with defined ferrite nanostructures - Kirchberg, Kristin; Justus Liebig University Giessen (My University, 2018)
The present thesis deals with the synthesis and characterization of nanostructured, phase-pure ferrite materials (MFe2O4) concerning their potential use in photocatalysis and photoelectrochemistry. The cubic spinel magnesium and zinc ferrite (MgFe2O4 and ZnFe2O4) and the orthorhombic calcium ferrite (CaFe2O4) were chosen as photocatalyst materials due to their composition of earth-abundant and non-toxic elements. They exhibit band gaps of 1.9 eV 2.0 eV[2,3], which allows to perform photocatalytic reactions under visible light excitation. While MgFe2O4 and CaFe2O4 are reported to be n-type and p-type semiconductors, respectively, contradictory reports were published on the band positions and semiconducting behavior of ZnFe2O4. Thus, this thesis aims to clarify these characteristics for the three chosen compounds.Solution-based synthesis procedures were selected on the basis of literature reports[4,5] to produce nanoparticles and mesoporous thin films of the selected ferrite compounds. For nanoparticle synthesis, a microwave-assisted approach was chosen. Furthermore, methods for post-synthetic and in situ production of colloidal solutions were developed. This offers the possibility to study the interplay of colloidal stability, the nature of surfactants and the resulting efficiency for photocatalytic degradation processes.To create mesoporous thin films, a dip-coating approach was applied investigating different block-copolymers used as porogens. The synthesis procedure was optimized with regard to the activity under visible light. By this means, conclusions on the connection between the pore morphology and crystallinity of mesoporous thin films and their photoelectrochemical performance was possible.Special focus was put on the phase purity of the synthesized ferrites, which was checked not only by X-ray diffraction (XRD), but also by Raman spectroscopy. Besides, various analytical methods such as spectroscopic tools, physisorption, photoelectrochemistry or synchrotron-based X-ray absorption techniques (XES, XANES, RIXS) were employed to achieve a detailed characterization and a deeper understanding of the photocatalytic and photoelectrochemical properties of the chosen ferrite materials.

Die vorliegende Arbeit beschäftigt sich mit der Synthese und Charakterisierung von nanostrukturierten, phasenreinen Ferritmaterialien (MFe2O4) in Hinblick auf ihre potentielle Anwendung in der Photokatalyse und Photoelektrochemie. Die kubischen Spinelle Magnesio- und Zinkferrit (MgFe2O4 und ZnFe2O4) und das orthorhombische Calciumferrit (CaFe2O4) wurden als photokatalytische Materialien ausgewählt aufgrund ihrer ressourcenreichen und ungiftigen Elemente. Die Materialien weisen Bandlücken zwischen 1.9 eV und 2.0 eV[2,3] auf, was die photokatalytische Anwendung unter Verwendung von sichtbarem Licht als Anregungsquelle ermöglicht. Während MgFe2O4 und CaFe2O4 als n-typischer bzw. p-typischer Halbleiter identifiziert wurden, gibt es in der Literatur widersprüchliche Berichte über die Bandpositionen und Halbleitercharakteristika des ZnFe2O4. Daher zielt diese Thesis auf die Aufklärung dieser Charakteristika für alle drei ausgewählten Verbindungen.Es wurden Synthesemethoden aus homogener Lösung anhand von Literaturstellen[4,5] ausgewählt, um Nanopartikel sowie mesoporöse Dünnfilme der ausgewählten Ferritmaterialien herzustellen. Für die Nanopartikelsynthese wurde ein mikrowellengestützter Ansatz gewählt. Außerdem wurden Methoden zur direkten und post-synthetischen Erzeugung kolloidaler Lösungen entwickelt. Dies ermöglicht die Erforschung der Zusammenhänge zwischen Kolloidstabilität, Art der Oberflächenreagenzien und der resultierenden Effizienz in photokatalytischen Abbaureaktionen.Um mesoporöse Dünnfilme herzustellen, wurde ein Tauchbeschichtungsverfahren verwendet und der Einfluss verschiedener Block-Copolymere als Porentemplate untersucht. Die Synthese wurde hinsichtlich der Aktivität der Materialien bei Bestrahlung mit sichtbarem Licht optimiert. Dadurch konnten Rückschlüsse auf den Zusammenhang zwischen Porenmorphologie und Kristallinität mesoporöser Dünnfilme und deren photoelektrochemischer Leistungsfähigkeit getroffen werden.Besonderer Fokus wurde auf die Phasenreinheit der synthetisierten Ferrite gelegt, was mittels Röntgendiffraktion (XRD) und Raman-Spektroskopie überprüft wurde. Außerdem wurden verschiedene Analysemethoden wie beispielsweise spektroskopische Methoden, Physisorption, Photoelektrochemie oder synchrotrongestützte Röntgenabsorptionstechniken (XANES, XES, RIXS) genutzt, um eine umfassende Charakterisierung der synthetisierten Proben zu ermöglichen und ein tieferes Verständnis über die photokatalytischen und photoelektrochemischen Eigenschaften der ausgewählten Materialien zu erhalten.
Nachhaltige solare Energieumwandlung mit definierten ferritischen Nanostrukturen
Keywords: Photoelektrochemie; Nanopartikel; Mesoporen; Ferrite; Photokatalyse; photoelectrochemistry; nanoparticles; mesopores; ferrites; photocatalysis; ddc:540